Building a Collaborative Understanding of Pathways to Adolescent Alcohol Misuse in a Mi’kmaq Community: A Process Paper - Zahradnik, Marc; Stevens, Doreen; Stewart, Sherry; Comeau, Nancy; Wekerle, Christine; Mushquash, Christopher (First Nations Child and Family Caring Society, 2007)
In April of 2006, a team of researchers consisting of both university and community partners from a Mi’kmaq reserve in Nova Scotia began the data-collection phase of a high school-based research study that had been two years in planning. The study examines the possible relationships between youth-reported childhood maltreatment, posttraumatic stress disorder (PTSD) symptoms, depressive symptoms, alcohol misuse, and resiliency factors. The aim of the research study is to provide information about adolescent alcohol misuse that is of practical beneﬁt to community-based service providers, and capable of making a scholarly contribution to the scientiﬁc study of the relations of anxiety/mood symptoms and addictive behaviours. The primary aim of this paper is to present both the context from which the project grew, and the steps involved in conducting research with our school partners and the community service providers. Asecondary aim is to present some of the preliminary data from the study, with a speciﬁc focus on resiliency.